Heavy metal composition of particulate matter in rural and urban residential built environments in Pakistan - Nasir, Zaheer A.; Colbeck, I.; Ali, Z.; Ahmed, S. (Pakistan Agricultural Scientists Forum, 2015)
Heavy metals in outdoor and indoor airborne particulate matter (PM) and dust in different residential built environmentsat two rural and one urban site in Pakistan were analysed. An eight stage non-viable impactor (Thermo Fisher Scientific Inc., USA) loaded with EMP 2000 glass microfiber filter papers (Whatman, England) was used to collect airborne PM.The indoordust samples (settled dust) were collected from different indoor surfaces (floor, cupboards) in living rooms and kitchens from houses at rural sites. The outdoor samples were collected from courtyards of the houses.At the urban site dust samples were also collected by the roads at 27 different locations around Lahoreand at a background site (University of Veterinary and Animal Sciences).Additionally, samples of dung cake, used as solid fuel, at one of the rural sites were taken.Heavy metals (Si, Al, Zn, Mn, Cu, Ni, Cd, Pb, Co and As) were determined by Graphite Furnace Atomic Absorption Spectrophotometer. At rural site I, in general, the concentrations of metals were higher outdoors than indoors, except for slightly higher indoor levels of Cu (0.85.g/m3 indoor: 0.56 outdoor.g/m3 ), Si (3.31.g/m3 indoor: 3.17 outdoor.g/m3 ) and Pb(11.99 ng/m3 indoor: 9.32 outdoor ng/m3 ). At the rural site II the mean concentration were higher outdoors than indoors, excluding Ni which was considerably higher indoors (55.68 ng/m3 ) than outdoors (31.91 ng/m3 ).At the urban site,outdoors, Si had the highest concentration (3.46 .g/m3 ) followed by Al, Zn, Mn, Cu, Ni, Cd, Pb and Co. Similarly, the indoor levels had a maximum contribution from Si (12.30 .g/m3 ) followed by Al, Mn, Zn, Cu, Cd, As, Pb, Ni and Co.With reference to dust at rural site I the top five metals outdoors were Si (708 mg/kg), Al, Cu, Zn and Pb (52 mg/kg) while, indoors Al was highest (281 mg/kg), followed by Si, Cu, Zn and Pb (57 mg/kg). At rural site II, both outdoors and indoors, Al (274 mg/kg – outdoor: 266 mg/kg - indoor), Si, Zn, Cu and Pb (61 mg/kg – outdoor: 80 mg/kg - indoor) were the five most abundant metals.The main five metals in decreasing order of their concentration in the road dust around Lahore were Si (686 mg/kg), Al, Cu, Zn and Pb (81 mg/kg). On the other hand, the dust samples from the background site showed Si (345 mg/kg) > Al >Pb> Cu > Zn (73 mg/kg). The airborne metal concentration of Pb was within the guideline value of WHO (0.5 .g/m3 ) but the levels of Mn, Cd and Ni were higher at all sites than the guidelines proposed by European Commission and WHO highlighting the risk of exposure to toxic metals in non-occupational environments.
Keywords: PM; dust; metals; household fuel; rural; urban; Pakistan